The Influence of Story Mapping Strategy on Reading Comprehension of Narrative Texts in Grade VIII Students of SMP Negeri 20 Pekanbaru - Hanna Rahmah Pratiwi; Rahmi Rahmi; Nurlisna Afrini; Salsabila Ramadhani; Adelia Purnawandira; Khusnul Sofia (Jurnal Ilmiah Profesi Pendidikan, 2026)
Reading comprehension is an essential skill in language learning because it helps students understand, analyze, and interpret written texts effectively. One strategy that can support students’ reading comprehension is the use of story mapping, which helps learners identify the structure and key elements of a narrative text. This study aims to determine the effect of the Story Mapping Strategy on students’ reading comprehension ability in narrative texts at SMPN 01 Kampar. The research used a quantitative approach with an experimental design. The subjects of the study were students of SMPN 01 Kampar. Data were collected through reading comprehension tests, observation, and documentation. The data were analyzed using a simple regression test with the help of statistical analysis. The results showed that the story mapping strategy had a positive and significant effect on students’ reading comprehension ability. This was proven by the significance value of 0.000 < 0.05 and the calculated t value of 3.981 > t table 1.699. In addition, the coefficient of determination (R Square) value of 0.353 indicates that the story mapping strategy contributed 35.3% to students’ reading comprehension ability. In conclusion, the story mapping strategy is effective in improving students’ reading comprehension ability in narrative texts. This strategy can be used as an alternative learning method to increase student engagement and understanding in reading activities.